The method for assessing and forecasting value of knowledge in SMEs: Research results - Justyna Patalas-Maliszewska; Hannes Werthner (Contemporary Economics, 2010)
Decisions by SMEs regarding knowledge development are made at a strategic level (Haas-Edersheim, 2007). Related to knowledge management are approaches to measure knowledge, where literature distinguishes between qualitative and quantitative methods of valuating intellectual capital. Although there is a quite range of such methods to build an intellectual capital reporting system, none of them is really widely recognized. This work presents a method enabling assessing the effectiveness of investing in human resources, taking into consideration existing methods. The method presented is focusing on SMEs (taking into consideration their importance for, especially, regional development). It consists of four parts: an SME reference model, an indicator matrix to assess investments into knowledge, innovation indicators, and the GMDH algorithm for decision making. The method presented is exemplified by a case study including 10 companies.
Keywords: 330